2019
DOI: 10.1093/annonc/mdz199
|View full text |Cite
|
Sign up to set email alerts
|

A multicentre, phase IIa study of zolbetuximab as a single agent in patients with recurrent or refractory advanced adenocarcinoma of the stomach or lower oesophagus: the MONO study

Abstract: BackgroundClaudin 18.2 (CLDN18.2) is physiologically confined to gastric mucosa tight junctions; however, upon malignant transformation, perturbations in cell polarity lead to CLDN18.2 epitopes being exposed on the cancer cell surface. The first-in-class monoclonal antibody, zolbetuximab (formerly known as IMAB362), binds to CLDN18.2 and can induce immune-mediated lysis of CLDN18.2-positive cells.Patients and methodsPatients with advanced gastric, gastro-oesophageal junction (GEJ) or oesophageal adenocarcinoma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
154
1
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 163 publications
(164 citation statements)
references
References 19 publications
(21 reference statements)
7
154
1
2
Order By: Relevance
“…To best of our knowledge, the present study is the largest systematic investigation of claudin 18.2 protein expression in EAC (n=485) in addition to the first study to detect claudin 18.2 expression in corresponding regional lymph node metastases using a commercially available monoclonal antibody, which was also used in other studies on gastric cancer (18)(19)(20)30). The present study demonstrated detectable claudin 18.2 expression in up to 18.4% of EAC cases.…”
Section: Discussionmentioning
confidence: 49%
See 3 more Smart Citations
“…To best of our knowledge, the present study is the largest systematic investigation of claudin 18.2 protein expression in EAC (n=485) in addition to the first study to detect claudin 18.2 expression in corresponding regional lymph node metastases using a commercially available monoclonal antibody, which was also used in other studies on gastric cancer (18)(19)(20)30). The present study demonstrated detectable claudin 18.2 expression in up to 18.4% of EAC cases.…”
Section: Discussionmentioning
confidence: 49%
“…Claudin 18.2 is an interesting tight-junction protein that may be therapeutically modifiable and whose relevance is currently being tested in studies on gastric cancer (16,(18)(19)(20)(21)28). In these studies, the response to therapy is associated with the measurable presence of the protein in the tumor (16,(18)(19)(20)(21)30). This may make claudin 18.2 a relevant biomarker, as we have known for years with programmed death-ligand 1, HER2/neu or hormone receptors in breast carcinoma.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…This antibody was demonstrated to mediate cancer cell death through antibody-dependent cellular cytotoxicity (ADCC) and complement-dependent cytotoxicity (CDC). In several early clinical trials for the treatment of advanced gastric cancer (GC), zolbetuximab alone or in combination with standard chemotherapy significantly prolonged survival with acceptable safety and tolerability [8,9].…”
Section: Introductionmentioning
confidence: 99%